Patient-Reported Cognitive Outcomes Following Cardiac Surgery: A Descriptive Review. (28th February 2021) - Robinson, Amanda; Pituskin, Edith; Norris, Colleen M
A descriptive review was conducted to evaluate the evidence of cognitive patient-reported outcome measures (PROMs) following cardiac surgery. The search of electronic databases resulted in 400 unique manuscripts. Nine studies met the criteria to be part of the final review. Results of the review suggest that there are few validated PROMs that assess cognitive function in the cardiac surgical population. Furthermore, PROMs have not been used to assess overall cognitive function following cardiac surgery within the past decade. However, one domain of cognitive function—memory—was described, with up to half of patients reporting a decline postoperatively. Perceived changes in cognitive function may impact health-related quality of life and a patient's overall view of the success of their surgery. Early identification of cognitive changes measured with PROMs may encourage earlier intervention and improve patient-centered care. In clinical practice, nurses may be in the best position to administer PROMs preoperatively and postoperatively.